Transient Fault Detection in Networked Control Systems. (12th November 2014) - Huang, Xiong-Feng; Zhou, Chun-Jie; Huang, Shuang; Huang, Kai-Xin; Li, Xuan
Transient faults appear unpredictablly and frequently in networked control systems (NCSs), which directly affect the safety of system. However, they can not be accurately identified due to various kinds of causes, so the detection of them needs more systematic and comprehensive system knowledge. Hence, a hierarchical and systematic detection approach based on function, behavior, and structure (FBS) models is proposed in this paper. The FBS models are established according to systematic knowledge of NCSs. And the transient faults are excavated in node level and system level, in which parameter match and model-based detections are employed. Moreover, the key implementation aspects of the proposed approach in NCSs are detailed on parameterization of FBS models, criteria, and feature parameters of faults, fault monitoring, fault detection, and real-time scheduling considering fault detection. At last, a simulation platform of a networked control liquid mixer system is described by Architecture Analysis and Design Language (AADL), and a transient fault is injected before the sample task in the node for fault detection. The simulation results show that the faults are exposed in the gradual detection hierarchies and the effectiveness of the detection scheme is quite promising.